AUTOMATIC SCORING SYSTEM DESIGN FOR SHOOTING USING TEMPLATE MATCHING ALGORITHM - Hari Harmaen (Pusat Penelitian Informatika - LIPI, 2012)
This paper presents an Automatic Scoring System (ASS) using image processing method for processing the image of shooting target and bullet trail. Compared with other methods, such as acoustic method, image processing method is more efficient. Grab Cut and Template Matching Algorithm will be used in the background segmentation and positioning the bullet trail. prototype ASS applications built using IP Camera, EMGU CV and C#, is divided into two modules, namely camera calibration module and score module. Based on the results of testing on the target paper 10m air rifle image, compared with manual / visual by officers, ASS application provide better score. 1.67 % scoring discrepancy occurred due to the poor quality of shooting target paper used.